The Tumor Necrosis Factor Superfamily Members TNFSF14 (LIGHT), Lymphotoxin β and Lymphotoxin β Receptor Interact to Regulate Intestinal Inflammation - Giles, Daniel A.; Zahner, Sonja; Krause, Petra; Van Der Gracht, Esmé; Riffelmacher, Thomas; Morris, Venetia; Tumanov, Alexei; Kronenberg, Mitchell (Frontiers in Immunology, 2018)
Over 1.5 million individuals in the United States are afflicted with inflammatory bowel disease (IBD). While the progression of IBD is multifactorial, chronic, unresolved inflammation certainly plays a key role. Additionally, while multiple immune mediators have been shown to affect pathogenesis, a comprehensive understanding of disease progression is lacking. Previous work has demonstrated that a member of the TNF superfamily, TNFSF14 (LIGHT), which is pro-inflammatory in several contexts, surprisingly plays an important role in protection from inflammation in mouse models of colitis, with LIGHT deficient mice having more severe disease pathogenesis. However, LIGHT is a single member of a complex signaling network. It signals through multiple receptors, including herpes virus entry mediator (HVEM) and lymphotoxin beta receptor (LTR); these two receptors in turn can bind to other ligands. It remains unknown which receptors and competing ligands can mediate or counteract the outcome of LIGHT-signaling during colitis. Here we demonstrate that LIGHT signaling through LTBR, rather than HVEM, plays a critical role in the progression of DSS-induced colitis, as LBR deficient mice exhibit a more severe disease phenotype. Further, mice deficient in LTab do not exhibit differential colitis progression compared to WT mice. However, deletion of both LIGHT and LTab but not deletion of both LTab and LTBR resulted in a reversal of the adverse effects associated with the loss of LIGHT. In sum, the LIGHT/LTab/LTBR signaling network contributes to DSS colitis, but there may be additional receptors or indirect effects, and therefore, the relationships between these receptors and ligands remains enigmatic.